2014
DOI: 10.1111/febs.12902
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA H19/miR‐675 axis represses prostate cancer metastasis by targeting TGFBI

Abstract: Prostate cancer is a leading cause of cancer-related mortality in men worldwide and there is a lack of effective treatment options for advanced (metastatic) prostate cancer. Currently, limited knowledge is available concerning the role of long non-coding RNAs in prostate cancer metastasis. In this study, we found that long non-coding RNA H19 (H19) and H19-derived microRNA-675 (miR-675) were significantly downregulated in the metastatic prostate cancer cell line M12 compared with the non-metastatic prostate epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
212
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(217 citation statements)
references
References 39 publications
5
212
0
Order By: Relevance
“…Many studies using cell culture systems and mouse models have shown that H19 can function either as an oncogene [25][26][27] or a tumor suppressor. 28,29 Recently, H19 RNA transcripts have been detected in a majority of patientderived premalignant lesions of cervical cancer. 21 Whether H19 is actively involved in the development of cervical cancer and how it works remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies using cell culture systems and mouse models have shown that H19 can function either as an oncogene [25][26][27] or a tumor suppressor. 28,29 Recently, H19 RNA transcripts have been detected in a majority of patientderived premalignant lesions of cervical cancer. 21 Whether H19 is actively involved in the development of cervical cancer and how it works remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…H19 is highly expressed during embryogenesis and is strongly downregulated after birth (23,24). Emerging evidence also indicates that the increased expression of H19 is commonly detected in a broad spectrum of pathological conditions, such as various malignancies (25)(26)(27), and after estrogen treatment (28) or exposure to hypoxia (29). H19 represses embryonic placental growth and trans regulates a network of imprinted genes during fetal development (23,30), but its role in cancer development can be tumor suppressive or oncogenic, depending on cellular content and tumor type (25,29,31).…”
mentioning
confidence: 99%
“…Previous studies have demonstrated the important roles that lncRNAs serve in cancer tissues (16)(17)(18). Although dysregulated lncRNAs have been implicated in numerous types of cancer, the specific mechanisms underlying their role in these pathologies has yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%